A Decision Algorithm Is Not Superior to Clinician Judgment to Determine Need for Peripheral vs Central Venous Catheterization. Issue 3 (June 2019) - Panter, Melissa; Olson, DaiWai M.; Stutzman, Sonja E.; Aiyagari, Venkatesh
Abstract : ABSTRACT: Background: Venous access, via a midline peripheral catheter (midline) or a peripherally inserted central catheter, is used regularly in the neurointensive care unit as a means for prolonged infusion of drugs or medications. There is little research on how to choose the appropriate access device to use in this setting. The aim of this study is to trial an algorithm to assist clinicians in determining which device to use, as a way to reduce patient complications such as central line–associated bloodstream infection and deep vein thrombosis. Methods: This quality improvement initiative included both retrospective and prospective data. A retrospective chart review was performed, and data were analyzed for variables associated with decision making between the 2 access devices. An algorithm was developed to assist clinicians with deciding between midline access and peripherally inserted central catheter access. Results: A total of 325 charts were reviewed (126 retrospective and 109 prospective). Results show no significant differences in the demographic characteristics of either group. Before intervention, clinicians chose the correct access device 86% of the time, whereas after the intervention, clinicians chose the correct device 78% of the time ( P = .06). Conclusion: The results of this study indicate that the quality improvement intervention and algorithm decision-making tool did not improve accuracy of use of access devices. Abstract : Supplemental digital content is available in the text.